Associations between longitudinal changes in sleep disturbance and depressive and anxiety symptoms during the COVID‐19 virus pandemic among older women with and without breast cancer in the thinking and living with breast cancer study. (22nd March 2022) - Bethea, Traci N.; Zhai, Wanting; Zhou, Xingtao; Ahles, Tim A.; Ahn, Jaeil; Cohen, Harvey J.; Dilawari, Asma A.; Graham, Deena M. A.; Jim, Heather S. L.; McDonald, Brenna C.; Nakamura, Zev M.; Patel, Sunita K.; et al.
Abstract: Purpose: Several studies have reported sleep disturbances during the COVID‐19 virus pandemic. Little data exist about the impact of the pandemic on sleep and mental health among older women with breast cancer. We sought to examine whether women with and without breast cancer who experienced new sleep problems during the pandemic had worsening depression and anxiety. Methods: Breast cancer survivors aged ≥60 years with a history of nonmetastatic breast cancer ( n = 242) and frequency‐matched noncancer controls ( n = 158) active in a longitudinal cohort study completed a COVID‐19 virus pandemic survey from May to September 2020 (response rate 83%). Incident sleep disturbance was measured using the restless sleep item from the Center for Epidemiological Studies‐Depression Scale (CES‐D). CES‐D score (minus the sleep item) captured depressive symptoms; the State‐Anxiety subscale of the State Trait Anxiety Inventory measured anxiety symptoms. Multivariable linear regression models examined how the development of sleep disturbance affected changes in depressive or anxiety symptoms from the most recent prepandemic survey to the pandemic survey, controlling for covariates. Results: The prevalence of sleep disturbance during the pandemic was 22.3%, with incident sleep disturbance in 10% and 13.5% of survivors and controls, respectively. Depressive and anxiety symptoms significantly increased during the pandemic among women with incident sleep disturbance (vs. no disturbance) ( β = 8.16, p < 0.01 and β = 6.14, p < 0.01, respectively), but there were no survivor‐control differences in the effect. Conclusion: Development of sleep disturbances during the COVID‐19 virus pandemic may negatively affect older women's mental health, but breast cancer survivors diagnosed with the nonmetastatic disease had similar experiences as women without cancer. Abstract : In this longitudinal study, the development of sleep disturbances during the COVID‐19 virus pandemic may have negatively affected older women's mental health by increasing symptoms of depression and anxiety. Breast cancer survivors diagnosed with non‐metastatic disease had similar experiences during the pandemic as women of similar age without cancer.